MENTHA SPİCATA L. SUBSP. SPİCATA (LAMİACEAE) BİTKİSİNİN MORFOLOJİK, ANATOMİK, PALİNOLOJİK VE BAZI KİMYASAL ÖZELLİKLERİNİN ARAŞTIRILMASI - AYDIN, FERHAT (Fırat Üniveristesi, 2012)
Bu çalışmada, Elazığ ve çevresinde doğal olarak yetişen Mentha spicata subsp. spicata'ya ait 6 farklı lokaliteden farklı fenolojik dönemlere ait çiçekli ve çiçeksiz örneklerden toplanarak dış morfolojik, anatomik, palinolojik ve uçucu yağları analiz edilerek kemotaksonomik yönden değerlendirilmiştir. Alttüre ait örneklerin morfolojik ve anatomik karakterleri ve polen karakteri ışık mikroskobu yardımıyla belirlenmiştir. Çalışılan örneklerin polen şekli sferoidal yapıda olup, ornementasyon retikulattır. Polen apertürünün ise hexacolpat olduğu tespit edilmiştir. Çiçekli ve çiçeksiz Mentha spicata subsp. spicata örneklerinden su distilasyonu ile elde edilen uçucu yağlar GC ve GC-MS ile analiz edilmiştir. Analiz sonucunda uçucu yağ veriminin 100 gr. kuru örnekte 1.0 ? 3.2 ml. arasında olduğu, tanımlanan 22 - 59 tane bileşenin toplam yağın % 88.7 - % 90.94' ünü oluşturduğu tespit edilmiştir. Ayrıca en yüksek bileşenin çiçeksiz örneklerde % 16.2, ile Trans-Caryophyllene iken çiçekli örneklerde % 18.1, ile 1.8-Cineole' olup. Kemotip tayini açısından önemli olan diğer majör bileşenlerin ise; Limonene (% 8.07 - 15.1), Piperitenone oxide (% 11.6), Pulegone (% 2.53 ? 7.56)'dur. Morfolojik ve anatomik özellikler bakımından ise ?Türkiye Florası? ve diğer araştırmacıların çalışmalarıyla uygunluk gösterdiği görülmüştür.Anahtar Kelimeler: Lamiaceae, Mentha spicata, Kemotaksonomi, Morfoloji, Anatomi.

In this study, the samples with flowered and non-flowered samples of the plant named Mentha spicata subsp. spicata which grows in and around Elazığ naturally have been collected and evaluated from the view point of chemotaxonomical features by conducting analysis on their essential oils as well as by taking into account of matters regarding their morphological, anatomical and palinological properties. The morphological and anatomical character and the polen characters of those samples belonging to the sub-species have been identified with the help of a light microscope. The polen forms of the samples on which surveys have been conducted are in the structure of sphyroeroidal and the ornamentations are reticulate. It has been discovered that the polen aperture is hexacolpat. The essential oils which are obtained by means of the method water distillation of the flowered and non-flowered samples of the plant named Mentha spicata subsp. spicata have been implemented the analysis process by means of the apparatus called GC and GC-MS. Consequently, as a result of those analysis, it has been discovered that the amount of the essential oil obtained from 100 gr. of dry sample is between 1.0 ? 3.2 ml and also the total amount of the oil in the defined 22-59 constituents is 88.7 % - 90.94 %. Moreover, it has been observed the maximum amount of constituents in the non-flowered samples is 16.2 % trans-Caryophyllene and the flowered samples contain 18.1 - 1.8 % Cineole. From the view point of the determination of chemo-type, the other major constituents are as follows: Limonene (8.07 %-15.1), Piperitenone oxide (11.6%), Pulegone (2.53?7.56 %). It has been observed that they display conformity from the view point of morphological and anatomical features with the ?Flora of Turkey? and the conclusions of those researches conducted by other research teams.Key Words: Lamiaceae, Mentha spicata, Chemotaxonomy, Morphology, Anatomy.
Research on the morphological, anatomical, palinological and some chemical features of the plant named Mentha spicata L. subsp. spicata (Lamiaceae)
Keywords: Botanik